Major and trace elemental concentration from sediment core EW0408-85JC and IODP Site 341-U1419 in intermediate-water depth from the Gulf of Alaska, Northeast Pacific - Du, Jianghui; Mix, Alan C; Haley, Brian A; Belanger, Christina L; Sharon (PANGAEA, 2022)
Here we report the sediment major and trace element geochemistry at two water depths in the Gulf of Alaska, Northeast Pacific, spanning the last ~50 kyr. These data were used to reconstruct past ocean deoxygenation and regional volcanism. Site EW0408-85JC and co-located IODP Site 341-U1419 are from the intermediate water depth (682 m). Elemental concentration data were collected using ICP-MS and ICP-OES at Oregon State University.
Keywords: Deoxygenation; Major and trace elements; redox sensitive metals